Cutaneous Rosai-Dorfman disease: a case report of disease limited only to skin (Dermatology Reports, 2021)
Rosai – Dorfman disease is a disorder of histiocytic proliferation that can affect almost every organ. Skin may be involved in about 10% cases, but only 3% of patients have skin lesions exclusively. Patients with CRDD usually are healthy, without leading constitutional or other symptoms. Etiology of this disease is unclear, but it might be triggered by an infectious agent such as Herpesvirus 6 and Epstein-Barr virus, there is also predisposition to autoimmune diseases, hematological malignancies. In our case patient was diagnosed with Borrelia burgdorferi infection. Any known association between this infection and Rosai – Dorfman disease was not described before. The disease may manifest in any age group. The differential diagnosis includes Langerhans cell histiocytosis, metastasis, Hodgkin’s lymphoma and other diseases. Disease usually resolves spontaneously over a period of months to years. Treatment should be administered in non-responsive or multiple relapsing cases. Also, it is very important to take into consideration the patient’s expectations and aesthetic appearance before making a treatment decision. Various treatment options are described, including surgical excision, cryotherapy, corticosteroids, antibiotics, Methotrexate, Dapsone. In our case, we used CO2 laser treatment successfully. To our knowledge, this is only the second case where CRDD lesions were treated successfully with CO2 laser.